Psychological Elements of The Actors As an Intangible Factor in The Co-Creation Process - Mia Rahma Romadona; Rendi Febrianda; Sigit Setiawan (STI Policy and Management Journal, 2022)
The studies that investigate the intangible factors that influence the success of co-creation, including the psychological aspects of the engaged actors' individual psychology, have not been well addressed. The intangible components, particularly the psychological aspects have gained little attention as many studies concentrate on tangible factors. The purpose of this study is to look into the psychological aspects of the actors as an intangible factor in the co-creation process between the Indonesian company PT X and the Indonesian Public Research Institute Y (PRI Y) through using Gerlink LIPI High Flow Nasal Cannula 01 (GLP HFNC 01) as a technological innovation. This study used a case study strategy and qualitative method to obtain in-depth data and to determine a more precise saturation point. The results show that personal proximity as a psychological aspect of interpersonal contact is the primary determinant of co-creation formation. Pleasant communication and personal engagement are crucial factors in establishing co-creation among industry, public R&D institutes, and consumers. The actors involved in the co-creation demonstrate that the individual's characters have a significant impact to foster the co-creation process such as open-mindedness, information-seeking, team leadership, interpersonal communication, and teamwork. Keywords: character, psychology, co-creation, commitment, communication, innovation, researcher, industry